"Not Everything That Shakes Is a Seizure": Making the Determination of Test Article–Induced Convulsions in Toxicology Studies. (November 2018) - Gauvin, David V.; Zimmermann, Zachary J.; Yoder, Joshua; Baird, Theodore J.
Spontaneous unexpected events occasionally develop during the course of rodent preclinical toxicology studies. The presentation of serious adverse events on animal studies may require notification of these events to the Food and Drug Administration if the events are most likely the direct result of test article administration. Classical conditioning of emotional responses may occur over the course of a repeat-dose study and clinical observation calls of "convulsions" are reported to the study director and/or staff veterinarians. In the current heightened environment of most research laboratories related to general animal welfare issues, it is imperative to have an action plan that will help to elucidate the potential origins of these motor events. We provide 10 factors that should be considered to help the study director determine the most likely cause of these motor attacks as being organic or psychogenic in origin.